The Role of Non-Governmental Organizations in Advancing Peace Education in Selected Barangays in Zamboanga del Sur: A Case Study - Bucayon – Simbajon, Darlyn; Pingki-an, Mary Jane (Journal of Interdisciplinary Perspectives, 2025)
This case study explores the role of non-governmental organizations (NGOs) in advancing peace education in selected barangays of Zamboanga del Sur, Philippines. The study aims to provide insights into the specific challenges and strategies of NGOs promoting peace education at the local level. Data were collected using semi-structured interviews with representatives from two NGOs actively engaged in peace education initiatives across multiple barangays. Thematic analysis revealed that although these organizations are dedicated to fostering peace, maintaining Indigenous culture, and engaging in community service, they face several obstacles: (1) Indigenous children's lack of interest and awareness, as well as Indigenous leaders' lack of peace education knowledge and skills; (2) schedule conflicts and limited funding (3) noncompliance with requirements, and (4) lack of support from partner organizations. To cope with these challenges, the selected NGOs involve Indigenous leaders in program planning and implementation, encourage community involvement and support, and customize programs to the specific needs and customs of the community. This highlights the significance of adaptability and inclusivity in promoting peace education and fostering sustainable change within the community they serve. The findings underscore the importance of adaptability and inclusivity in promoting peace education and achieving sustainable change within the communities served.